The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acs.jpcc.1c07848
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Crystal Defects, Oxygen Vacancies, and Phase Transition of Ir-TiO2

Abstract: The impact of iridium (Ir) doping on the oxygen vacancies, relative stability, crystallite size, surface area, and anatase-to-rutile transition of TiO 2 was comprehensively investigated in this study. Ir-doped TiO 2 (Ir-TiO 2 ) was synthesized through a sol−gel technique, and the samples were annealed in the temperature range of 400−700 °C. Density functional theory calculations showed that the energy cost of an oxygen vacancy formation for Ir-TiO 2 was lower, as compared to that of the pristine TiO 2 , with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The phase transition from anatase to rutile occurs at about 600 °C. 71,72 However, we found that the phase composition of the catalyst was sustained even when the calcination temperature increased up to 800 °C. It can be speculated that the graphite-like carbon layers suppress the phase transition temperature from anatase to rutile of more than 200 °C.…”
Section: Resultsmentioning
confidence: 83%
“…The phase transition from anatase to rutile occurs at about 600 °C. 71,72 However, we found that the phase composition of the catalyst was sustained even when the calcination temperature increased up to 800 °C. It can be speculated that the graphite-like carbon layers suppress the phase transition temperature from anatase to rutile of more than 200 °C.…”
Section: Resultsmentioning
confidence: 83%
“…The anatase grains act as nucleation sites to facilitate the phase transformation to rutile . However, there are no significant changes in the BJH adsorption pore size, which implicates the uniform dispersion of dopants on the TiO 2 surface …”
Section: Resultsmentioning
confidence: 99%
“…41 However, there are no significant changes in the BJH adsorption pore size, which implicates the uniform dispersion of dopants on the TiO 2 surface. 42 3.5. XPS.…”
Section: Betmentioning
confidence: 99%
“…As shown in Figure 2a, the high-resolution Ir 4f XPS spectrum of complex 1 is centered at 61.74 eV (Ir 4f 7/2 ) and 64.76 eV (Ir 4f 5/2 ), which can be attributed to metallic Ir species. 27,28 Similarly, 1@NWF-g-MAH exhibits two peaks at 61.97 eV (Ir 4f 7/2 ) and 64.79 eV (Ir 4f 5/2 ), manifesting the existence of Ir(III) complexes on the substrate. Furthermore, the high-resolution N 1s XPS spectrum of complex 1 can be divided into three peaks (Figure 2b), corresponding to C− N�C (398.8 eV), tertiary nitrogen (N−(C) 3 ) (399.7 eV), and amino functional groups (−NH 2 ) (399.2 eV).…”
Section: Synthesis Of [Ir(cumr) 2 (Dabpy)] + @Nwf-g-mah Film (1@nwf-g...mentioning
confidence: 99%